Re/designing the writing center to support technical literacy initiatives - Getty, Matt, author; Amidon, Tim, advisor; Champ, Joe, committee member; Langstraat, Lisa, committee member (Colorado State University. Libraries, 2020)
Technology pervades most aspects of life and a level of technical prowess is all but required to participate in modern society. The increasing emphasis on STEM initiatives and "learning to code" often focuses on functional literacies and not, as Selber (2004) noted, "...on critical literacy as teachers of writing and communication think of" (p. 74). What is at stake in a critical technical literacy? Noble (2018) said in Algorithms of Oppression that "design[ing] technology for people without a detailed and rigorous study of people and communities, makes for the many kinds of egregious tech designs we see" (p. 70) and that "now more than ever, we need experts in the social sciences and digital humanities to engage in dialogue" (p. 13)—a technical dialogue, about how technologies are developed. Writing studies and writing center studies could find it beneficial to embrace new definitions of composing and technology rather than wait for them to make inroads to these fields. This study first recognizes how writing has grown beyond the conventional. Digital composing covers a broad spectrum from writing blog posts, designing websites, using photoshop, creating podcasts, and writing code. Vee (2017) argued in Coding Literacy that "[w]riting and programming are creative acts yet we've tried to label programming as engineering" (p. 123), and this study tries to understand what labeling programming as a form of writing alongside other digital composing ultimately means for places where writing takes place. This study focuses on writing centers, and seeks to extend Pemberton's (2003) four suggestions for "Planning for Hypertext in the Writing Center...Or Not" which suggested that writing centers can treat hypertexts (digital composing) like any other text, assume hypertext will not come into the writing center, use specialized tutors, or provide tutor training in order to serve students who enter the writing center looking to get assistance on these types of composing assignments. In order to do this, this study collected data from participatory design focus group sessions as well as from writing center (and similar space) websites. The data was coded into five different codes: Access / Technology, Discovery / Outreach, Career Readiness, Training, and Curriculum / Coursework. Comments in these categories were analyzed to identify how individual actors—students, writing centers, institutions—function to help or hinder students who engage with the writing center with digital composing. This study suggests that unless users believe they could be successful in engaging with the writing center with digital composing, it is unlikely that any of Pemberton's (2003) four suggestions will ever be relevant. While a successful engagement with digital composing could result from the use of typical writing center pedagogies, this needs to be clear to prospective users who may believe they require consultants and spaces with high levels of technical ability to help in their digital composing. This study suggests that peripheral texts—texts that suggest how a user can interact with a space—are one key area where the writing center could exercise its own agency and help users understand both that they can, and how they can engage with the writing center with digital composition and technology. Curricular and institutional changes may also aid in the re centering of the writing center to better support technical literacy initiatives throughout the university.
Keywords: digital literacies; digital composing; writing centers